Fiscal correction for economic growth: data analysis and suggestions - Mohan, Rakesh (2000)
Rapid economic growth is the only solution to the problem of poverty and such growth is not possible without significant fiscal correction. The key objective of fiscal reform has to be a reduction in public debt service payments. This article analyses data on state and central government revenues and expenditures to suggest ways to climb out of the debt trap. - Reproduced
Keywords: Economic growth